Dento-facial proportions analysis of maxillary anterior teeth in Khuisf dental students - Nasim Esnaashari Esfahani; Alireza Omrani; Mehrdad Barekatain; Marzieh Yavari (مجله دانشکده دندانپزشکی اصفهان, 2011)
Introduction: Shape and size of upper anterior teeth are important in dental and facial beauty. The aim of this study was to determine the correlation between dental and facial indexes and to evaluate whether there is a golden ratio and its relationship with the proportions measured.Materials and Methods: In this cross-sectional study, digital images of 34 female and 30 male dental students were taken at maximum smile in a similar manner. Then the images were assessed with Photoshop CS5 and ACDSee computer programs and measurements were made with AutoCAD 2011 software. Data was analyzed with independent t-test and means were compared with a constant.Results: The entire variable means did not demonstrate any significant differences between males and females (p value > 0.05). The inter-pupillary to inter-canine distance ratio did not reveal any significant differences with the golden proportion of 1.618 between males and females (p value > 0.05). Only the ratios of inter-pupillary, inter-canthus and inter-zygomatic distances to maxillary central widths in females, and the ratios of inter-zygomatic and inter-alar distances to maxillary central widths in males were not significant.Conclusion: Under the limitations of the present study, it was concluded that dento-facial proportions are not significantly different between males and females and the golden ratio applies in the inter-pupillary to apparent width of anterior maxillary teeth proportion. Facial indices are appropriate measures to measure the apparent width of anterior maxillary teeth and can be used as a standard for Iranian dentists and surgeons. Key words: Anterior teeth, Dental position, Diastema, Proportion.